Structural components of adolescent’s environmental awareness in a general education institution - V. Moshura (Науковий вісник Мукачівського державного університету. Серія "Педагогіка та психологія", 2023)
The relevance of the problem of developing adolescents’ environmental awareness is conditioned upon the need to instil in students the concepts of nature management and nature conservation in a general education institution to develop healthy behaviour towards nature and its resources, and an appropriate level of value attitude towards natural and cultural monuments. The purpose of the research is to identify the main structural components, factors and conditions for the development of environmental awareness of adolescents in educational institutions, and to identify opportunities for using the latest information technologies for the development and promotion of environmental awareness. To comprehensively explore the subject of environmental awareness, the research uses analytical, statistical and comprehensive research methods. The main results of the study are to identify the types and specific features of the development of environmental awareness in adolescents. The research presents the criteria of environmental competence: cognitive, value and activity-practice. The structure of the ecological consciousness of pupils of general educational institutions based on cognitive, connotative, axiological and perceptual-emotional levels is determined. The research considers the possibilities of using information technologies that will help to develop a new programme of adolescent consciousness-raising, namely, modern systems for displaying and disseminating information, social networks, and online conferences and online courses. The practical significance of the research work lies in the establishment of a new programme for the development of a healthy attitude of adolescents towards the environment and the establishment of basic values that should be used to preserve existing natural and cultural monuments, and in classes on environmental awareness in secondary schools, training courses and out-of-school education.